1
You visited us 1 times! Enjoying our articles? Unlock Full Access!
Question

# Complete the following table of products of two monomials: First → Second ↓ 3x –6y 4x2 –8xy 9x2y –11x3y2 3x –6y 4x2 –8xy 9x2y –11x3y2

Open in App
Solution

## First → Second ↓ 3x –6y 4x2 –8xy 9x2y –11x3y2 3x 3x × 3x = 9x2 3x × (–6y) = –18xy 3x × 4x2 = 12x3 3x × (–8xy)= –24x2y 3x × 9x2y = 27x3y 3x × (–11x3y2) = –33x4y2 –6y (–6y) ×3x = –18xy (–6y) × (–6y) = 36y2 (–6y) × 4x2 = –24 x2y (–6y) × (–8xy)= 48x y2 (–6y) × 9x2y= –54 x2y2 (–6y) × (–11x3y2) = 66 x3y3 4x2 4x2 × 3x= 12x3 4x2 × (–6y) = –24x2y 4x2 × 4x2 = 16x4 4x2 × (–8xy)= –32x3y 4x2 × 9x2y= 36x4 y 4x2 × (–11x3y2) = –44x5y2 –8xy (–8xy) × 3x = –24x2y (–8xy) × (–6y) = 48xy2 (–8xy) × 4x2 = –32x3y (–8xy) × (–8xy) = 64x2y2 (–8xy) × 9x2y= –72x3y2 (–8xy) × (–11x3y2) = 88x4y3 9x2y 9x2y × 3x= 27x3y 9x2y × (–6y) = –54x2y2 9x2y × 4x2 = 36x4y 9x2y × (–8xy)= –72x3 y2 9x2y × 9x2y= 81x4y2 9x2y × (–11x3y2) = –99x5 y3 –11x3y2 (–11x3y2) × 3x = –33x4y2 (–11x3y2) × (–6y) = 66x3y3 (–11x3y2) × 4x2 = –4x5y2 (–11x3y2) × (–8xy) = 88x4y3 (–11x3y2) × 9x2y= –99x5y3 (–11x3y2) × (–11x3y2) = 121x6y4

Suggest Corrections
0
Join BYJU'S Learning Program
Related Videos
Introduction
MATHEMATICS
Watch in App
Explore more
Join BYJU'S Learning Program